Design of Highly Porous Single‐Site Catalysts through Two‐Step Postsynthetic Modification of Mixed‐Linker MIL‐53(Al) - Gotthardt, Meike A.; Schoch, Roland; Brunner, Tobias S.; Bauer, Matthias; Kleist, Wolfgang (ChemPlusChem)
Keywords: General Chemistry

Synthesis and characterization of bimetallic metal–organic framework Cu–Ru-BTC with HKUST-1 structure - Gotthardt, Meike A.; Schoch, Roland; Wolf, Silke; Bauer, Matthias; Kleist, Wolfgang (Dalton Transactions)
A mixed-metal framework Cu–Ru-BTC with the formula Cu2.75Ru0.25(BTC)2·xH2O was successfully synthesized. Partial substitution of Cu2+ by Ru3+ in the paddlewheel structure was proven using X-ray absorption spectroscopy.
Keywords: Inorganic Chemistry

A Rhodium Triphenylphosphine Catalyst for Alkene Hydrogenation Supported on Neat Superparamagnetic Iron Oxide Nanoparticles - Dehe, Daniel; Wang, Lei; Müller, Melanie K.; Dörr, Gunder; Zhou, Zhou; Klupp-Taylor, Robin N.; Sun, Yu; Ernst, Stefan; Hartmann, Martin; Bauer, Matthias; Thiel, Werner R. (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Hydrolytic Stability and Hydrogen Peroxide Activation of Zirconium‐Based Oxoclusters - Faccioli, Francesco; Bauer, Matthias; Pedron, Danilo; Sorarù, Antonio; Carraro, Mauro; Gross, Silvia (European Journal of Inorganic Chemistry)
Keywords: Inorganic Chemistry

Base‐Free Non‐Noble‐Metal‐Catalyzed Hydrogen Generation from Formic Acid: Scope and Mechanistic Insights - Mellmann, Dörthe; Barsch, Enrico; Bauer, Matthias; Grabow, Kathleen; Boddien, Albert; Kammer, Anja; Sponholz, Peter; Bentrup, Ursula; Jackstell, Ralf; Junge, Henrik; Laurenczy, Gábor; Ludwig, Ralf; et al. (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

The Electronic Ground State of [Fe(CO)3(NO)]−: A Spectroscopic and Theoretical Study - Klein, Johannes E. M. N.; Miehlich, Burkhard; Holzwarth, Michael S.; Bauer, Matthias; Milek, Magdalena; Khusniyarov, Marat M.; Knizia, Gerald; Werner, Hans-Joachim; Plietker, Bernd (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

A series of amide functionalized isoreticular metal organic frameworks - Keceli, E.; Hemgesberg, M.; Grünker, R.; Bon, V.; Wilhelm, C.; Philippi, T.; Schoch, Roland; Sun, Y.; Bauer, Matthias; Ernst, S.; Kaskel, S.; Thiel, Werner R. (Microporous and Mesoporous Materials)
Keywords: Mechanics of Materials; Condensed Matter Physics; General Materials Science; General Chemistry

A Catalytic System for the Activation of Diorganozinc Reagents - Werner, Thomas; Bauer, Matthias; Riahi, Abdol Majid; Schramm, Heiko (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Polynuclear Iron(II)–Aminotriazole Spincrossover Complexes (Polymers) In Solution - Bräunlich, Irene; Sánchez-Ferrer, Antoni; Bauer, Matthias; Schepper, Rahel; Knüsel, Philippe; Dshemuchadse, Julia; Mezzenga, Raffaele; Caseri, Walter (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

HERFD-XAS and valence-to-core-XES: new tools to push the limits in research with hard X-rays? - Bauer, Matthias (Phys. Chem. Chem. Phys.)
This perspective accounts for the benefits of the high resolution hard X-ray spectroscopic methods HERFD-XANES and valence-to-core-XES.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy